Safety and effectiveness of post percutaneous coronary intervention physiological assessment: Retrospective data from the post-revascularization optimization and physiological evaluation of intermediate lesions using fractional flow reserve registry - Leone, Antonio Maria; Migliaro, Stefano; Zimbardo, Giuseppe; Cialdella, Pio; Basile, Eloisa; Galante, Domenico; Di Giusto, Federico; Anastasia, Gianluca; Vicere, Andrea; Petrolati, Edoardo; Di Stefano, Antonio; Campaniello, Giorgia; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background While the importance of invasive physiological assessment (IPA) to choose coronary lesions to be treated is ascertained, its role after PCI is less established. We evaluated feasibility and efficacy of Physiology-guided PCI in the everyday practice in a retrospective registry performed in a single high-volume and “physiology-believer” center. Materials and methods The PROPHET-FFR study (NCT05056662) patients undergoing an IPA in 2015–2020 were retrospectively enrolled in three groups: Control group comprising patients for whom PCI was deferred based on a IPA; Angiography-Guided PCI group comprising patients undergoing PCI based on an IPA but without a post-PCI IPA; Physiology-guided PCI group comprising patients undergoing PCI based on an IPA and an IPA after PCI, followed by a physiology-guided optimization, if indicated. Optimal result was defined by an FFR value ≥ 0.90. Results A total of 1,322 patients with 1,591 lesions were available for the analysis. 893 patients (67.5%) in Control Group, 249 patients (18.8%) in Angiography-guided PCI Group and 180 patients (13.6%) in Physiology-guided PCI group. In 89 patients a suboptimal functional result was achieved that was optimized in 22 cases leading to a “Final FFR” value of 0.90 ± 0.04 in Angiography-Guided PCI group. Procedural time, costs, and rate of complications were similar. At follow up the rate of MACEs for the Physiology-guided PCI group was similar to the Control Group (7.2% vs. 8.2%, p = 0.765) and significantly lower than the Angiography-guided PCI Group (14.9%, p < 0.001), mainly driven by a reduction in TVRs. Conclusion “Physiology-guided PCI” is a feasible strategy with a favorable impact on mid-term prognosis. Prospective studies using a standardized IPA are warrant to confirm these data.